Toponymy of Tourism Points in Makkah and Madinah Toponimi Tempat Wisata di Makkah dan Madinah - Fatimah - Azzahra; Moh Masruhi (JURNAL DIMENSI, 2022)
AbstractThis study aims to reveal aspects of the linguistic unit and the background of naming tourist attractions in Mecca and Medina. The problems discussed include the form of the linguistic unit and the background for the naming. This research uses descriptive qualitative analysis method. The data of this research were obtained through literature study and informants using the tapping method. The data was then analyzed using the syntactic theory of Ramlan (2005) and Chaer's naming (2013). The results showed that the form of linguistic units in the names of tourist attractions was divided into two, namely words and phrases. The word form is divided into two, namely 5 basic words and 11 affixed words, while for phrases are coordinating endocentric phrases and attributive endocentric phrases and totaling 9 phrases. The naming background is in the form of 5 mentions of the appearance of the earth, 4 names of characters and 5 places of origin. Keywords : name of tourist place, makkah, madinah, naming